SEARCH FOR TiO-BAND VARIABILITY OF COOL GIANT - Komarov, N. S.; Dorokhov, N. I.; Dorokhova, T. N. (Одеські астрономічні публікації, 2017)
The dissipation of acoustic energy and bombardement of high energy particles of TiO molecules can be sources of temperature "inversion" and nonstability of outer layers of atmospheres of cool giants. In 1993 the trial observations on variability of outer layers of the cool giant HD73665 was made at the Mt. Dushak-Erekdag station of Odessa Astronomical Observatory. For simultaneous observations in TiO-band and Johnson V-band, a split prism in the dual-channel photometer was used. The observations show quasi-periodical variations at the time scale of 2-12 min.